2020
DOI: 10.1038/s41419-020-2704-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced replication origin licensing selectively kills KRAS-mutant colorectal cancer cells via mitotic catastrophe

Abstract: To unravel vulnerabilities of KRAS-mutant CRC cells, a shRNA-based screen specifically inhibiting MAPK pathway components and targets was performed in CaCo2 cells harboring conditional oncogenic KRASG12V. The custom-designed shRNA library comprised 121 selected genes, which were previously identified to be strongly regulated in response to MEK inhibition. The screen showed that CaCo2 cells expressing KRASG12V were sensitive to the suppression of the DNA replication licensing factor minichromosome maintenance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The KRAS/LKB1 oncological genotype imposes metabolic vulnerability dependent on DNA synthesis ( 50 ). Moreover, KRAS -mutant cancer cells are sensitive to suppression of the DNA replication licensing factor MCM7 ( 51 ). In our study, we identified E2F targets — including several preRC genes — as downstream components of BCL6 in a KRAS -mutant background ( Figure 5 ), suggesting a unique role of BCL6 in regulating replication origins.…”
Section: Discussionmentioning
confidence: 99%
“…The KRAS/LKB1 oncological genotype imposes metabolic vulnerability dependent on DNA synthesis ( 50 ). Moreover, KRAS -mutant cancer cells are sensitive to suppression of the DNA replication licensing factor MCM7 ( 51 ). In our study, we identified E2F targets — including several preRC genes — as downstream components of BCL6 in a KRAS -mutant background ( Figure 5 ), suggesting a unique role of BCL6 in regulating replication origins.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, normal cells respond to licensing inhibitors by activating a licensing checkpoint and arresting temporarily in G1 phase ( Matson et al, 2019 ; Mcintosh and Blow, 2012 ). On the contrary, the genetically unstable cancer cells might possibly have a defective licensing checkpoint ( Shreeram et al, 2002 ; Nevis et al, 2009 ; Zimmerman et al, 2013 ; Gastl et al, 2020 ) while ectopic licensing of origins of replication outside G1 phase can cause genome re-replication ( Klotz-Noack et al, 2012 ; Muñoz et al, 2017 ). A similar mechanism of action has been suggested for a family of arylquinolin-amines that was identified as inhibitors of replication licensing, by preventing the tight ORC-DNA interaction required for MCM2-7 loading onto chromatin ( Gardner et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%